Comparison between the Nano-Silica Extracted from Date Palm Ash and Silicone Gel to Treat the Induced Second Degree Burn in Albino Rats Model - Ali Jameel Haichal; Prof. Amir I. Towfik (Diyala Journal for Veterinary Sciences, 2025)
This study explores the healing effects of nanosilica extracted from date palm on second-degree burns in white rats, comparing its efficacy with that of silicone gel, a commonly used treatment for burn injuries, and a control group that received no treatment. A total of 30 white rats were randomly divided into three groups, with each group consisting of 10 animals. The first group was treated with a 5% nanosilica, the second group received a topical application of silicone gel (Scarmed®), and the third group served as a control and received no treatment. All treatments were applied once daily for 7 days. The healing process was evaluated macroscopically and microscopically at 7, 14, and 21days post-treatment. The nanosilica-treated group showed accelerated wound healing, faster re-epithelialization, reduced inflammation, and minimal scarring compared to both the silicone gel-treated and control groups. The silicone gel-treated group showed moderate improvement in wound healing but lagged behind the nanosilica group, while the control group exhibited the slowest healing, with prolonged inflammation, less organized collagen deposition, and noticeable scarring. Histological examinations revealed enhanced collagen deposition, fibroblast activity, and tissue regeneration in the nanosilica-treated wounds, which were significantly better than those observed in the other two groups. These findings indicate that nanosilica, with its biocompatibility and regenerative properties, holds great promise as a natural, effective treatment for burn injuries, offering a viable alternative to traditional silicone-based treatments.